High‐Precision and High‐Flux Separation by Rationally Designing the Nanochannels and Surface Nanostructure of Polyamide Nanofiltration Membranes - Han Zheng; Zihao Mou; Yu Jie Lim; Narasimalu Srikanth; Wang Zhang; Sheng Guo; Rong Wang; Kun Zhou (Small Science, 2022)
High‐precision separation with increased water permeability is critical for efficient membrane‐based water treatment processes. To achieve high selectivity toward different targeted species while allowing rapid water transportation, the structure of the membrane polyamide selective layer requires delicate regulation. Herein, an effective approach to systematically expand the pore size of polyamide layers by incorporating ammonium ion‐modified carbon dots (CDs) into the polyamide network is developed. The ammonium ions with different alkyl chain lengths attached to the CDs create nanochannels of different sizes in the network to lower the energy barrier for water transportation while maintaining high selectivity to targeted species. When the alkyl chain length of the ammonium ions reaches eight carbon atoms (i.e., C8 ions), the amphiphilic C8‐CDs induce the formation of the ridged nanostructure on the membrane surface and hence the increased membrane filtration area. The resultant thin‐film nanocomposite (TFN) membrane, denoted as the TFN‐C8‐CDs membrane, demonstrates a higher Na2SO4 rejection of 98.9% and NaCl/Na2SO4 selectivity of 83.1 than the pristine polyamide membrane, together with a tripled pure water permeability of 29.0 L m−2 h−1 bar−1. Herein, a viable approach for ingeniously designing the nanochannels and surface nanostructure of polyamide membranes for more efficient filtration processes is provided.